The New Guarantee System for Monitoring Healthcare Services Delivery in Italy: technical remarks and recommendations - Signorelli, Carlo; Blandi, Lorenzo; Cuciniello, Rita; Calabretta, Rosaria; Pregliasco, Fabrizio; Odone, Anna; Gelatti, Umberto; Castaldi, Silvana; Pelissero, Gabriele (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Over the past 15 years, Italy’s National Health Service has been the object of increased governmental attention, due to the need to control public spending, reduce waste, and maintain acceptable levels of quality, accessibility and appropriateness of healthcare services. Methods. One of the key mechanisms to achieve this has been the implementation of performance assessment systems. Among these is the New Guarantee System, introduced in 2019, which utilizes 88 indicators across three key macro-areas — public health and prevention, primary health care, and hospital care — to assess the quality and equity of essential healthcare services. Results. This paper critically analyzes the 2025 New Guarantee System report, identifying strengths, limitations, and potential improvements for a more effective monitoring system. The findings reveal significant gaps in the current healthcare performance evaluation system. The reliance on descriptive statistics limits the ability to interpret healthcare outcomes accurately. The absence of indicators addressing chronic diseases, health inequalities, new technologies and qualitative patient experiences suggests the urgent need of a more comprehensive evaluation approach. Conclusions. To improve the healthcare performance evaluation system, it is recommended to incorporate more comprehensive indicators that address the identified gaps. Enhanced data integration, qualitative assessments, and an increased focus on chronic diseases and health disparities are essential to provide a more accurate evaluation of healthcare services